STUDENTS’ PERCEPTION OF NARRATIVE TEXT WRITING DIFFICULTY - Anggri Nurmawarni; Abdul Kamaruddin; Budi Budi (Tadulako University, 2022)
The purpose of this study was to determine the difficulties and causes of difficulties for class VIII students in writing narrative texts. This study uses a qualitative research design. The subjects of this study were students of class VIII B, totaling 20 students. In this study, data collection was carried out by distributing questionnaires and interviews. Based on the results of the analysis of questionnaires and interviews, it is known that students have difficulty in writing narrative texts. The difficulty lies in the tenses of the narrative text, the difficulty in placing punctuation and capital letters, and the difficulty in understanding the generic structure of the written narrative. The causes of difficulties in writing narrative texts are lack of vocabulary, lack of writing practice, and the last cause is the obstacles experienced by students when learning online. The solution that the researchers gave to the students was that students were expected to learn more about narrative text material and increase English vocabulary so that students could more easily understand and writing narrative texts.